Two-fraction anaerobic fermentation of grass waste - Maroušek, Josef (Journal of the science of food and agriculture, 2013)
BACKGROUND: Waste from public green areas represents large quantities of grassy phytomass. The grass is usually utilised by composting, combustion or anaerobic fermentation. However, the classical composts are time-demanding, the quality of accelerated composts is low, combustion is under increasing criticism and conventional anaerobic fermentation requires high investment. RESULTS: A new method of two-fraction anaerobic fermentation of grass waste consisting from a hot maceration, up-flow anaerobic sludge blanket reactor, steam explosion, horizontally stirred batch anaerobic fermentors and a charcoal kiln, all run on waste heat from a co-generation unit was investigated on a commercial scale. CONCLUSION: The results shows that due to faster energy utilisation the two-fraction technology requires smaller fermentors and hence the technology is approximately one-third less costly than conventional systems, with 4 years shorter payback time. Additionally, huge amounts of charcoal are produced. However, the process control and optimisation is more demanding.
Keywords: Animals; odpad tekutý - odstraňování; listy rostlin; Charcoal; Waste Disposal, Fluid; Plant Leaves; fermentace; Refuse Disposal; Poaceae; Technology; technologie; dřevěné a živočišné uhlí; náklady a analýza nákladů; lipnicovité; Fermentation; odpadky - odstraňování; Anaerobiosis; zvířata; Soil; anaerobióza; půda; Costs and Cost Analysis